Misperceiving the Beliefs of Others: How Pluralistic Ignorance Contributes to the Persistence of Positive Security Analyst Reactions to the Adoption of Stock Repurchase Plans - Zhu, David H.; Westphal, James D. (Organization Science, 2011)
We consider how a social psychological bias referred to as pluralistic ignorance occurs among security analysts and how this bias may lead to behavioral conformity and isomorphism in analysts' reactions to the adoption of a particular organizational policy, namely, stock repurchase plans. Our theory suggests why (1) there may be a systematic tendency for analysts to underestimate the extent to which other analysts share their reservations about repurchase plans (i.e., reservations about whether plans reflect well on the performance prospects of adopting firms), such that (2) analysts conform to other analysts and issue more positive earnings forecasts and stock recommendations in response to the adoption of repurchase plans despite having private reservations about whether the plans reflect well on adopting firms. We also contend that analysts are less likely to underestimate the extent to which others share their reservations about repurchase plans to the extent that they have frequent communication ties to other analysts. Whereas prior neoinstitutional research on conformity and isomorphism has primarily adopted a cognitive perspective in which actors conform to the behavior of others based on their understandings of a particular policy or practice (i.e., they take the value of the policy for granted or infer the value of the policy from others' prior decisions), we develop a social psychological perspective on isomorphism wherein actors imitate others based on their biased perceptions of others' beliefs about the policy. We also extend perspectives on institutional persistence by explaining why constituents may continue to publicly endorse a policy despite having private reservations about the policy's efficiency benefits.